How to get your point across in 30 seconds-or less - Frank, Milo O. 1928- (Simon & Schuster Audio, 1999)
"Milo Frand, former CBS television talent and casting head, who teaches communication skills to the top executives of such Fortune 500 companie as AT&T, IBM and Bank of America, shows you how easy it is to get your point across in 30 seconds-and get what you want. Whether you are writing a letter or memo, making a speech, asking for a raise or promotion, making a point, or closing a sale, HOW TO GET YOUR POINT ACROSS IN 30 SECONDS OR LESS is and invaluable training tool for both business people and professionals. You will be amazed at your enhanced efectiveness when you discover how to use the 30 second message to get exactly what you want."